PELATIHAN PEMBUATAN ES KRIM BAYAM BAGI IBU-IBU DI KELURAHAN JATIPULO, PALMERAH, JAKARTA BARAT - Rianita Pramitasari; Dennys Kurniawan Lianto; Hugo Alexander; Rakhdiny Sustaningrum; Syarief Darmono (Jurnal Kewirausahaan dan Bisnis, 2021)
The majority of the population in Jatipulo village, Palmerah, Wes Jakarta, work as laborers with incomes below the minimum wage of the city. Meanwhile, most of the women are housewives who have no income. The community service aimed to train their skill and foster an entrepreneurial spirit by processing spinach into ice cream. The ice cream processing aims to extend the shelf life of spinach and increase its selling value. The methods used in this empowering program were teaching and training, with the following activities: (1) teaching of spinach nutrient content, spinach benefits, and the theory of the processing of spinach ice cream, (2) the practice of making spinach ice cream production, and (3) monitoring and evaluation. In general, training activities have been running smoothly without any sign of constraints. Participants play an active role during the training in both the discussion and practice. The driving factor of the activity is the curiosity of the participants to innovate the processing of spinach into products that have more value. Based on the monitoring results, the participants had several times made spinach ice cream for their consumption. It can be concluded that the program has provided insight into new knowledge related to spinach and the processing of spinach into ice cream that has more value. Intensive and sustained mentoring is required for the women who want to make their spinach ice cream as one of the products for entrepreneurship.Keywords: Ice Cream, Spinach, Training